Actin Remodeling Defects Leading to Autoinflammation and Immune Dysregulation - Papa, Riccardo; Penco, Federica; Volpi, Stefano; Gattorno, Marco (Frontiers in Immunology, 2021)
A growing number of monogenic immune-mediated diseases have been related to genes involved in pathways of actin cytoskeleton remodeling. Increasing evidences associate cytoskeleton defects to autoinflammatory diseases and primary immunodeficiencies. We reviewed the pathways of actin cytoskeleton remodeling in order to identify inflammatory and immunological manifestations associated to pathological variants. We list more than twenty monogenic diseases, ranging from pure autoinflammatory conditions as familial Mediterranean fever, mevalonate kinase deficiency and PAPA syndrome, to classic and novel primary immunodeficiencies as Wiskott-Aldrich syndrome and DOCK8 deficiency, characterized by the presence of concomitant inflammatory and autoimmune manifestations, such as vasculitis and cytopenia, to severe and recurrent infections. We classify these disorders according to the role of the mutant gene in actin cytoskeleton remodeling, and in particular as disorders of transcription, elongation, branching and activation of actin. This expanding field of rare immune disorders offers a new perspective to all immunologists to better understand the physiological and pathological role of actin cytoskeleton in cells of innate and adaptive immunity.